Exo-axial, Endo-axial and Exo-equatorial Anomeric Effects for Mono and Dihalo[1,4]dioxane in Solvent and Gas Phases - Arshadi, S.; Shad, Y.; Emami, J.; Bekhradnia, A.R.; Yazdani, O.; Pahlevan, R.; Qajar, F.; Rajaee, M.; Badeli, A.; Ebrahimzadeh, M.A. (Asian Journal of Chemistry, 2010)
The stability order of 9 possible diastereomers of 2,6-di-halo[1,4]- dioxane (series 1') and 6 diastereomers of halo[1,4]dioxane (series 2') are calculated and compared them with 2,6-dihalocyclohexane (series 1) and halocyclohexane (series 2). Endo-axial (nO→σ*C-X-A), exo-axial (nX-A→σ*C-O) and exo-equatorial (nX-E&rarrr;σ*C-O) anomeric effects (AE) on structural parameters as well as relative energies are studied. Generally, exo-equatorial anomeric effects for equatorial halogens has more efficient energetically and structurally effects in series 1' in comparison to series 2'. Whereas, for axial halogens opposite order are found for "net endo" anomeric effects. The solvation analysis illustrates that in polar solvents free solvation energy gaps are larger for series 2' in comparison to their corresponding gap of series 2.